Synthesis of novel 3,5-disubstituted-2-oxindole derivatives as antitumor agents against human nonsmall cell lung cancer - Nesi, G.; Sestito, S.; Mey, V.; Ricciardi, S.; Falasca, Marco; Danesi, R.; Lapucci, A.; Breschi, M.; Fogli, S.; Rapposelli, S. (American Chemical Society, 2013)
This study was aimed at investigating the antitumor activity of novel 2-oxindole derivatives against a well-characterized human nonsmall cell lung cancer (NSCLC) cell line. Test compounds produced an antiproliferative activity in the low micromolar/submicromolar range of concentrations and significantly induced typical apoptotic morphology with cell shrinkage, nuclear condensation and fragmentation, and rupture of cells into debris in a relatively low percentage of A549 cells. Cell cycle arrest occurred at the G1/S phase (1a and 2), and Akt phosphorylation was significantly inhibited at Thr308 and Ser473. The most active compound (1a) has an IC50 6-fold lower than the Akt inhibitor, perifosine. These data suggest that the new compounds may be cytostatic and may have maximum clinical effects in NSCLC patients who do not respond to EGFR inhibitors. These findings prompt us to further explore the oxindole structure as leading scaffold to design new molecules with potent antitumor activity against NSCLC. © 2013 American Chemical Society.